Efektivitas Pelaksanaan Program Kartu Pelaku Usaha Kelautan dan Perikanan (KUSUKA) bagi Nelayan di Kecamatan Banggai Utara - Findra Riadi; Yacob Noho Nani; Raihan Hanasi (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to determine the effectiveness of the implementation of the Marine and Fisheries Business Actor Card Program (KUSUKA) for fishermen in North Banggai District, Banggai Laut Regency, and to identify the factors influencing its implementation. The study employed a qualitative approach with a descriptive research design. The research focus referred to Budiani’s (2009) program effectiveness theory, which includes target accuracy, program socialization, achievement of program objectives, as well as program monitoring and evaluation. Data collection techniques consisted of interviews, observations, and documentation, while data analysis used the interactive model of Miles and Huberman through data reduction, data presentation, and conclusion drawing. The results showed that the implementation of the KUSUKA Program in North Banggai District was fairly effective but not yet fully optimal. The targeting accuracy of the program was in accordance with the established criteria; however, the coverage of beneficiaries remained low. Program socialization had been carried out, yet the community’s understanding of the program mechanisms was still limited. The KUSUKA Program also provided benefits in the form of access to government assistance and protection for fishermen, although the distribution of benefits was not evenly distributed. In addition, program monitoring and evaluation activities were still constrained by limited human resources and operational budgets. Therefore, the effectiveness of the KUSUKA Program still requires improvement, particularly in terms of program coverage, socialization, and monitoring implementation.